2006
DOI: 10.1038/sj.bjc.6603236
|View full text |Cite
|
Sign up to set email alerts
|

A pilot clinical study of Δ9-tetrahydrocannabinol in patients with recurrent glioblastoma multiforme

Abstract: D 9 -Tetrahydrocannabinol (THC) and other cannabinoids inhibit tumour growth and angiogenesis in animal models, so their potential application as antitumoral drugs has been suggested. However, the antitumoral effect of cannabinoids has never been tested in humans. Here we report the first clinical study aimed at assessing cannabinoid antitumoral action, specifically a pilot phase I trial in which nine patients with recurrent glioblastoma multiforme were administered THC intratumoraly. The patients had previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
225
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(231 citation statements)
references
References 26 publications
5
225
0
1
Order By: Relevance
“…strated a marked reduction in Ki67 staining within the tumor (66). This observation together with the very promising results observed in cell cultures and laboratory animals (8 -12) suggest that administering cannabinoids alone or in conjunction with existing chemotherapeutic agents may be a promising treatment strategy for aggressive cancers of various origins.…”
Section: Discussionmentioning
confidence: 57%
“…strated a marked reduction in Ki67 staining within the tumor (66). This observation together with the very promising results observed in cell cultures and laboratory animals (8 -12) suggest that administering cannabinoids alone or in conjunction with existing chemotherapeutic agents may be a promising treatment strategy for aggressive cancers of various origins.…”
Section: Discussionmentioning
confidence: 57%
“…Notably, not only in vitro cell culture systems are subject to this treatment response but also in vivo experiments using either xenografts or syngeneic mouse models have shown the potential of cannabinoids as anticancer agents, without observing major psychoactive or immune-suppressive effects (8,13). Recently, the first clinical study using Δ 9 -tetrahydrocannabinol (THC) in severe cases of glioblastoma has been reported (14).…”
Section: Introductionmentioning
confidence: 99%
“…24 Aside from one clinical trial with end-stage glioblastoma multiforme patients, THC has not been studied clinically as a treatment for malignancy. 8 Unfortunately, there are many claims on the internet about the "curative" effects THC can have for cancer patients, where these articles often cite ongoing research articles. However, these articles and websites extrapolate in vitro study results and preclinical work into humans without any basis in fact.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…1,[5][6][7] To date, there has only been one clinical trial looking at the antitumoural activity of cannabinoids on terminal human patients harbouring actively growing recurrent gliomas. 8 Hence, this review will outline the current evidence on the antiproliferative effects of endocannabinoids in the male genitourinary malignancies, including renal, prostate, bladder, and testicular cancers, and look to explore the possible role of future human clinical trials in the field.…”
Section: Introductionmentioning
confidence: 99%